1992
DOI: 10.1128/aac.36.10.2125
|View full text |Cite
|
Sign up to set email alerts
|

Microbiological efficacy and pharmacokinetics of prophylactic antibiotics in liver transplant patients

Abstract: The pharmacokinetics of perioperative systemic antibiotics and the microbiological effectiveness of oral nonabsorbable antibiotics started immediately prior to surgery were studied in 18 adult patients undergoing liver transplantation. All patients received cefotaxime, 2 g intravenously, at 6-h intervals during surgery and then at 8-h intervals thereafter for 48 h; eight patients also received ampicillin at the same dose and schedule. This regimen produced levels of antibiotics in blood that appeared appropria… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

1993
1993
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 36 publications
0
15
0
Order By: Relevance
“…No studies have assessed the optimal duration of antimicrobial prophylaxis in liver transplantation. Although antimicrobials have been administered in studies for five days 937,944,946,949,[957][958][959] and seven days, 964 the majority of recent studies have limited the duration of prophylaxis to 72 hours, 981 48 hours, 936,943,945,952,955,956,960,961,967,970,979,980,991 36 hours, 981 24 hours, 935,948,962,970 and a single dose, 963 with no apparent differences in early infection rates. A prospective, nonrandomized, controlled study found no difference in bacterial infections within the first three months after liver transplantation in patients receiving cefotaxime and ampicillin as short-term antimicrobial prophylaxis for two to three days, compared with long-term prophylaxis for five to seven days.…”
Section: Liver Transplantationmentioning
confidence: 97%
See 3 more Smart Citations
“…No studies have assessed the optimal duration of antimicrobial prophylaxis in liver transplantation. Although antimicrobials have been administered in studies for five days 937,944,946,949,[957][958][959] and seven days, 964 the majority of recent studies have limited the duration of prophylaxis to 72 hours, 981 48 hours, 936,943,945,952,955,956,960,961,967,970,979,980,991 36 hours, 981 24 hours, 935,948,962,970 and a single dose, 963 with no apparent differences in early infection rates. A prospective, nonrandomized, controlled study found no difference in bacterial infections within the first three months after liver transplantation in patients receiving cefotaxime and ampicillin as short-term antimicrobial prophylaxis for two to three days, compared with long-term prophylaxis for five to seven days.…”
Section: Liver Transplantationmentioning
confidence: 97%
“…936,943,949,955,956,967,968,980,990,991 These studies used combinations of nonabsorbable antibacterials (aminoglycosides, polymyxin B or E), antifungals (nystatin, amphotericin B), and other antimicrobials (cefuroxime in suspension) administered orally and applied to the oropharyngeal cavity in combination with systemically administered antimicrobials. Results are conflicting, with no differences in patient outcomes (e.g., infection rates, mortality) or cost and concerns of increasing gram-positive infections with potential resistance in several studies 939,955,956,980,991 and others with positive results.…”
Section: Liver Transplantationmentioning
confidence: 99%
See 2 more Smart Citations
“…The rationale for the use of OSBD is based on the fact that Gram‐negative bacteremias carry a higher mortality rate than those caused by Gram‐positive organisms. To achieve optimal elimination of aerobic Gram‐negative bacilli from the gastrointestinal tract with OSBD, the regimen has to be started at least 3 days prior to transplant ( 20–23). This can present a problem with compliance in patients that have to wait prolonged periods for a donor (up to one year) and in cases of fulminant hepatic failure that require transplantation in less than 3 days.…”
Section: Prevention Of Bacterial Infectionsmentioning
confidence: 99%